Hematopoietic stem cell transplantation for children with acute myeloid leukemia: results of the AML SCT-BFM 2007 trial - Sauer, Martin Günther; Greil, Johann (Leukemia, 2020)
AML SCT-BFM 2007 was the first hematopoietic stem cell transplantation (HCT) trial in Germany to comply with the European Clinical Trials Directive, and aimed to standardize pediatric HCT for acute myeloid leukemia (AML) across centers in Germany, Austria, and the Czech Republic. Children with high-risk features and a good early response achieving a complete first remission (CR-1) and those in CR-2 after a first relapse were stratified to receive HCT from a matched donor after myeloablative conditioning consisting of busulfan, cyclophosphamide, and melphalan. Four-year EFS and OS were 61 and 70%. Cumulative incidence of relapse (CIR) was 22%. TRM was 15% and correlated with age reaching 9% (SE 3%) in children younger than 12 years and 31% (SE 9%) in older children and adolescents. Children with poorly responding primary disease or relapse were allocated to receive early HCT after a cytoreductive regimen with fludarabine, amsacrine, and cytarabine, followed by reduced intensity conditioning and prophylactic donor lymphocyte infusions. Four-year EFS and OS were 49 and 53%. CIR was 38% and TRM 11%. For patients with primary poor response disease, early use of RIC HCT followed by prophylactic DLI can induce long-term remissions in more than 50% (EFS 46% (SE 9%)).